Understanding public views on electric vehicle charging: A thematic analysis - Colin Ashby; David Weir; Peter Fussey (Transportation Research Interdisciplinary Perspectives)
Studies have identified EV charging as a major barrier to EV adoption. We analyse public opinion related to EV charging to understand perceived charging-related barriers and successes. We extract EV charging related posts from Twitter using a pipeline based on BERTopic and Large Language Models, with manual review, to create a thematic structure driven by the data, then analyse these themes using message sentiment and volume. Strong interest and positive sentiment exists around charging technologies and public infrastructure deployment, indicating hope for the future of EV adoption and public deployment meeting demand. Negative opinion exists around blocked and broken chargers, the impact of cold climate, EV ”subsidies” and since 2020 a weakening of the economic argument for EVs. Home charging is viewed enthusiastically by those with access to it and as a barrier and inequity by those that do not. Green issues received the least interest of all our themes.